2022
DOI: 10.3389/fvets.2022.918933
|View full text |Cite|
|
Sign up to set email alerts
|

Moringa oleifera Leaf Powder Dietary Inclusion Differentially Modulates the Antioxidant, Inflammatory, and Histopathological Responses of Normal and Aeromonas hydrophila-Infected Mono-Sex Nile Tilapia (Oreochromis niloticus)

Abstract: This study aimed to detect the impact of Moringa oleifera leaf powder dietary inclusion on the antioxidant and innate immune responses of mono-sex Nile tilapia fingerlings. A total of 180 fingerlings were allocated in a random method into three groups with triplicate each. One group (1st group) received the control diet (basal diet (BD) free of moringa) and the other groups (2nd and 3rd) fed BD containing M. oleifera leaf powder at 5 and 10% of the diet, respectively. After 6 weeks of feeding, fish were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These results demonstrated that magnolol could reduce the excessive inflammation caused by A. hydrophila and A. veronii by enhancing the host anti‐inflammatory response. EI‐Kassas et al (2022) also found that feeding Nile tilapia with a diet containing Moringa oleifera leaf powder can lower the infection‐associated inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
“…These results demonstrated that magnolol could reduce the excessive inflammation caused by A. hydrophila and A. veronii by enhancing the host anti‐inflammatory response. EI‐Kassas et al (2022) also found that feeding Nile tilapia with a diet containing Moringa oleifera leaf powder can lower the infection‐associated inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
“…Our results clearly indicated that the moringa' immunomodulation in Nile tilapia was dose-dependent and affected by fermentation. Higher M. oleifera concentrations have been previously found to decrease phagocytic activity [ 62 ]. This agrees with our results, as increased levels of M. oleifera beyond the 5% level have a negative effect on the overall health status, producing an immunosuppressive effect on the host, as observed in the MO 10% treated group.…”
Section: Discussionmentioning
confidence: 99%
“…So recently, many studies have focused on using new alternative techniques which safer for the health of people, animals, and environment to minimize or replace antibiotics. One of these alternatives is medicinal plants and bacteria [ 10 13 ]. These medicinal plants are economical and have effective compounds that improve fish immunological responses and to enhance fish growth and general health [ 10 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of these alternatives is medicinal plants and bacteria [ 10 13 ]. These medicinal plants are economical and have effective compounds that improve fish immunological responses and to enhance fish growth and general health [ 10 , 14 16 ]. Leaf extracts from medicinal plants have been applied in several attempts to offer antioxidant protection and detoxification to fish living in contaminated environments [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%